Incident Response. Computer Forensics Toolkit - Schweitzer, Douglas (Wiley Publishing, 2011)
* Incident response and forensic investigation are the processes of detecting attacks and properly extracting evidence to report the crime and conduct audits to prevent future attacks * This much-needed reference covers the methodologies for incident response and computer forensics, Federal Computer Crime law information and evidence requirements, legal issues, and working with law enforcement * Details how to detect, collect, and eradicate breaches in e-mail and malicious code